nNOS-derived NO modulates force production and iNO-derived NO the excitability in C2C12-derived 3D tissue engineering skeletal muscle via different NO signaling pathways - Mosqueira, Matias; Scheid, Lisa-Mareike; Kiemel, Dominik; Richardt, Talisa; Rheinberger, Mona; Ollech, Dirk; Lutge, Almut; Heißenberg, Tim; Pfitzer, Lena; Engelskircher, Lisa; Yildiz, Umut; Porth, Isabel (Frontiers in physiology, 2022)
Nitric oxide (NO) is a bioactive gas produced by one of the three NO synthases: neuronal NOS (nNOS), inducible (iNOS), and endothelial NOS (eNOS). NO has a relevant modulatory role in muscle contraction; this takes place through two major signaling pathways: (i) activation of soluble guanylate cyclase and, thus, protein kinase G or (ii) nitrosylation of sulfur groups of cysteine. Although it has been suggested that nNOS-derived NO is the responsible isoform in muscle contraction, the roles of eNOS and iNOS and their signaling pathways have not yet been clarified. To elucidate the action of each pathway, we optimized the generation of myooids, an engineered skeletal muscle tissue based on the C2C12 cell line. In comparison with diaphragm strips from wild-type mice, 180 myooids were analyzed, which expressed all relevant excitation-contraction coupling proteins and both nNOS and iNOS isoforms. Along with the biochemical results, myooids treated with NO donor (SNAP) and unspecific NOS blocker (L-NAME) revealed a comparable NO modulatory effect on force production as was observed in the diaphragm strips. Under the effects of pharmacological tools, we analyzed the myooids in response to electrical stimulation of two possible signaling pathways and NO sources. The nNOS-derived NO exerted its negative effect on force production via the sGG-PKG pathway, while iNOS-derived NO increased the excitability in response to sub-threshold electrical stimulation. These results strengthen the hypotheses of previous reports on the mechanism of action of NO during force production, showed a novel function of iNOS-derived NO, and establish the myooid as a novel and robust alternative model for pathophysiological skeletal muscle research.
Gesehen am 15.09.2022